An effective approach to project management in the non-profit sector through crowdfunding (Economics and region, 2024)
The article is devoted to an innovative approach in project management in the non-profit sector using crowdfunding. The essence and foundations of the project management mechanism, as well as the content and purpose of the functioning of non-profit organizations, have been defined. The growing relevance of crowdfunding as a financing mechanism, especially in the context of limited resources, high competition and the need for sustainable development of non-profit organizations, has been investigated. The important role of crowdfunding in mobilizing financial resources through online platforms, emphasizing transparency, public involvement and the development of trust between donors and recipients, has been emphasized. Key stages and principles for the successful implementation of crowdfunding projects in non-profit organizations have been proposed. Adherence to these principles will help non-profit organizations create long-term support for their initiatives. The concept and role of non-profit organizations in solving social issues has been highlighted. The essence of crowdfunding as a technology of social financing, which provides greater transparency, reduces dependence on large investors and state funding, and is based on mass participation, has been determined. Strategic internal and external communication using modern tools, transparency, flexibility, monitoring of the crowdfunding project at all stages of its implementation, feedback, reporting and adaptation of the project to the needs of donors, targeted, rational and effective use of collected funds are crucial in achieving the success of a crowdfunding project of non-profit organizations. Particular attention has been paid to the significance of building trust among stakeholders and the importance of regular communication to ensure accountability. The practical application of these principles is crucial for establishing sustainable partnerships with donors and supporters. The gradual popularization of crowdfunding in Ukraine and the functioning of some platforms, however, the lack of proper development in this sector, which is observed in more developed economies, has been noted. The article identifies the high significance of expanding the use of crowdfunding in Ukraine, emphasizing the potential of this tool for stimulating social and economic change.
Keywords: non-profit organization; crowdfunding; crowdfunding project; crowdfunding campaign; financing; online platforms